The Role Of Self-Control in Mediating The Influence of Descriptive Norms and Academic Stress on Intentioncyberloafing - Sukino Subiyantoro; Sudarwati; Ida Aryati DPW (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to:analyze the influence of descriptive norms on cyberloafing, academic stress on cyberloafing, self-control on cyberloafing, descriptive norms on self-control, academic stress on self-control, descriptive norms on cyberloafing through self-control as a mediating variable, and analyze the influence of academic stress on cyberloafing through self-control as a mediating variable for training participants at BLK Karanganyar. This research uses quantitative methods by distributing questionnaires (e-questionnaires) and statistical or computational methods using SmartPLS (Partial Least Square) software with Structural Equation Modeling (SEM) equation models. This research was conducted on 117 samples who were training participants at BLK Karanganyar in 2023 Young Graphic Designer Training Program and Position GMAW Welding Plate Welder Training Program (3G/PF). The research results show that only descriptive norms were found to have a positive effect on cyberloafing, while academic stress and self-control were found to have no effect. However, in terms of self-control, academic stress was found to have a negative effect on participants' self-control. Meanwhile, the mediating variable results of self-control succeeded in mediating the relationship between academic stress and cyberloafing.